Unraveling the Structural Transformation of Wood Lignin During Deep Eutectic Solvent Treatment - Wang, Shuizhong; Li, Helong; Xiao, Ling-Ping; Song, Guoyong (Frontiers in Energy Research, 2020)
Deep eutectic solvents (DESs) can efficiently promote the efficiency of cellulose enzymatic hydrolysis through the removal of lignin component in lignocellulosic biomass pretreatment. Unraveling the fundamental structural variant of lignin during DES treatment would facilitate to understand the DES-based biomass pretreatment in a clear perspective. Herein, an enzymatic mild acidolysis lignin (EMAL) and a series of β-O-4 lignin model compounds were employed to be treated with choline chloride (ChCl)/lactic acid (LA) (1:2) DES, from which the structural variant of all lignin fractions can be realized in a detailed version. The β-O-4 linkages, existing in either realistic lignin or model compounds, could be cleaved by ChCl/LA, thus leading to the decrease of molecular weight and the rise of hydroxyl groups. The influence of reaction temperature and time was also examined in view of some key structural parameters. Experimental evidences from model compounds confirmed that the repolymerization occurs with the depolymerization of lignin, which may account for the low production of monomeric products during DES treatment.